A profile of the global auto industry : innovation and dynamics - Smitka, Michael (Industry profiles collection., 2017)
This is the first book on the global auto industry viewed through the lens of technology. We start by tracing how innovation shaped the first century of its history. We then examine the industry's shifting footprint in Europe and North America, and the rise of new producers, particularly China. Succeeding chapters emphasize the role of suppliers in what is now a high-tech industry. We describe new forms of collaboration that challenge traditional supply chain relations, analyzing regulation as a driver of innovation, and the enabling role of the materials science revolution, such as the shift of steel from a commodity to a highly engineered product. We cover innovations in management, from computer-aided engineering, roadmapping, and just-in-time methods to the evolving role of workers and public policy. We finish with an overview of electric vehicles, shared mobility, and autonomous vehicles, concluding that they will not prove disruptive.